The shelf life of buffalo meat marinated with pomegranate (Punica granatum) peel extract - Rasuli, Nur; Bintoro, Valentinus Priyo; Purnomoadi, Agung; Nurwantoro, Nurwantoro (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The purpose of this study was to investigate how pomegranate peel extract (PPE) can prevent lipid oxidation, peroxide value, and pathogenic bacteria growth in buffalo meat. Materials and Methods: PPE and buffalo meat were employed in this investigation. The buffalo meat marinated with PPE was evaluated by refrigerating it at a temperature of 5°C ± 1°C on days 0, 4, 8, 12, and 16. PPE was added to buffalo meat at a rate of 0% as a control (K0), 0.50% (K1), 1.00% (K2), 1.50% (K3), and 2.00% (K4). Results: The addition of PPE lowered the total plate count, peroxide value, lipid, and pH between treatments and storage period (p < 0.05). PPE’s high concentration of polyphenols, flavonoids, antioxidants, and antibacterial substances may decrease lipid oxidation, peroxide production, and bacterial growth rate. Conclusions: Marinating buffalo meat in PPE may help maintain the meat’s freshness while being stored at a refrigerator temperature (5°C ± 1°C). J. Adv. Vet. Anim. Res., 8(4): 612–618, December 2021 http://doi.org/10.5455/javar.2021.h552